Women's issues. Issue 4 (19th September 2020) - Keni, Ravish; Mostacci, Barbara; Kiteva‐Trenchevska, Gordana; Licchetta, Laura; Ignjatova, Liljana; Thomas, Sanjeev; Meador, Kimford J.
Abstract: Special considerations are required for women with epilepsy. These include issues such as catamenial exacerbation, concerns for contraception, teratogenesis (including both anatomical and neurodevelopmental effects), and other concerns for pregnancy complications such as increased seizures or adverse obstetric outcomes. In this manuscript, several cases are presented and discussed addressing some of the important issues in the management of women with epilepsy.